Determinants of Safety Citizenship Behavior: A Case Research of Operation Employees at Kereta Api Indonesia (Persero) - Iqbal T. Iskandar; Deden Sutisna M. N. (PT. Publikasiku Academic Solution, 2025)
Train accident statistics show that risky behavior continues to occur, both in the form of violations of standard operating procedures and poor safety behavior by Indonesian Railways (KAI) operational staff, which can lead to accidents. Therefore, a more in-depth examination of the variables that influence Safety Citizenship Behavior (SCB) is needed. This research aims to analyze the effect of safety procedures and safety motivation on SCB, with safety leadership as a moderating variable. Data was collected from August to December 2024 using the Partial Least Square (PLS) based Structural Equation Model (SEM) technique in Bandung Operation Area 2. The research sample consisted of 143 randomly selected employees. The results showed that social capital has a significant influence on safety citizenship behavior, while safety motivation does not show a significant influence. However, safety leadership was proven to moderate the influence of safety motivation on SCB, increasing the effectiveness of safety motivation in encouraging this behavior. These findings demonstrate the importance of developing an appropriate safety leadership model to improve safety behavior and reduce dangerous activities in KAI. By understanding the factors that influence SCB, it is hoped that KAI can improve operational safety and employee welfare.